EFEKTIVITAS PENGGUNAAN MEDIA SEMPOA BERBASIS INTEGRASI ETIKA TERHADAP PEMAHAMAN KONSEP DASAR MATEMATIKA SEKOLAH DASAR - Pebrianti; St. Ramlah Makmum; Anggun Aprilianti S.Sansi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of abacus media integrated with ethical values in improving elementary mathematics concept understanding among first-grade students at SD Inpres BTN IKIP II. The problem addressed is the low understanding of basic mathematical concepts due to their abstract nature and the limited integration of ethical values in learning. This research employed a quantitative approach with a pre-experimental one-group pretest-posttest design involving 20 students. Data were collected through tests, observation, and documentation, and analyzed using the Shapiro-Wilk normality test and Paired Samples T-Test. The results showed normal data distribution (p = 0.113) and a significant difference between pretest and posttest scores (p < 0.002), indicating improved learning outcomes after treatment. In conclusion, abacus media integrated with ethical values is effective in enhancing mathematical concept understanding while fostering discipline, honesty, and responsibility. It is recommended that teachers consistently integrate character-based learning media into classroom instruction.